Preparation method of MIL-101-acrylate compound for negative photoresist
By combining MIL-101-acrylate composite with components such as epoxy resin, the preparation process of negative photoresist is simplified, and the shortcomings of existing photoresist in terms of edge neatness, resolution and stability are solved. , achieving more efficient and reliable photoresist production.
Patent Information
- Application Number
- CN202411734752.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Existing negative photoresist has shortcomings in edge neatness, resolution and stability, and is difficult to control during the modification process, resulting in by-products and polymer chain winding problems, affecting chip quality.
The MIL-101-acrylate composite is combined with components such as epoxy resin, and negative photoresist is prepared through hydrothermal reaction and high-temperature sealing reaction, which simplifies the preparation process and avoids the control problem of polymerization reaction.
Improves the edge neatness, resolution and storage stability of photoresist, simplifies the production process, reduces process challenges, and improves the photolithography success rate and product accuracy.
Smart Images

Figure CN119414661A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of semiconductor chips and chemical industry, and in particular to a MIL-101-acrylate composite and a negative photoresist and a preparation method thereof. Background Art
[0002] Photoresists can be divided into two types: positive photoresists and negative photoresists, depending on how the exposed areas are treated during the development process. Positive photoresists are able to transfer patterns to the photoresist layer under ultraviolet light. The exposed parts will decompose and can be dissolved by the developer, while the unexposed parts are insoluble and therefore retained. The advantage of this photoresist is that it has a higher resolution and does not expand. In contrast, after ultraviolet light irradiation, the exposed areas of negative photoresists will cross-link and become insoluble in the developer, while the unexposed parts can be dissolved. This photoresist has good heat resistance and is suitable for the manufacture of high-power and special devices. It is usually used in the final packaging stage of chips to provide insulation and protection. However, negative photoresists are difficult to remove, and due to the uneven molecular weight distribution of their resins, their uniformity and stability are poor, and their resolution is also low.
[0003] In order to improve the performance of negative photoresists, some technologies use single-molecule solid epoxy resins or small-molecule resins to enhance the sensitivity and development speed of photocuring. However, these resins have high processing costs and are difficult to prepare into high-viscosity liquids, which may lead to the peeling and loss of photoresists, affecting the overall quality of the chip. In previous studies, the preparation of photoresists requires the modification of resins, but the polymerization reaction during the modification process is difficult to control, and may produce by-products and polymer chain entanglement problems. In addition, the modified epoxy resin is easy to cross-link under light, resulting in the inactivation of the photoresist and increasing the difficulty of storage. Under the conditions of photosensitive reaction, the uniformity of the cross-linking degree is also difficult to ensure, which may lead to reduced edge neatness and increased defective rate. Finally, since negative photoresists require multiple exposures, the requirements for adhesion are high, and modified small-molecule resins may not meet this requirement. Therefore, it is particularly important to design a photoresist with neat edges, high resolution, and certain self-healing properties. Summary of the invention
[0004] The present invention aims to solve the defects of negative photoresists in the prior art and introduces a new type of negative photoresist product. The product has neat edges, high resolution, self-repairing ability and topological identification marking function, which improves the success rate of photolithography and avoids the process challenges caused by resin modification.
[0005] The present invention provides a method for preparing a MIL-101-acrylate composite for negative photoresist, which is characterized by comprising the following steps:
[0006] Preparation of MIL-101-acrylate composite:
[0007] S1. Dissolve chromium nitrate nonahydrate (Cr(NO3)3·9H2O) and terephthalic acid (C8H6O4) in deionized water at a molar ratio of 1:1, add hydrofluoric acid and stir evenly to form a mixed solution. Then, transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and perform a hydrothermal reaction at 220°C for 9 hours. After the reaction is completed, let the reactor cool naturally to room temperature, and after post-processing steps such as centrifugation, washing and drying, MIL-101 is finally obtained.
[0008] S2. MIL-101, polymethylphenylsiloxane and hydroxyethyl acrylate are mixed in a ratio of 1:0.1:10, and one or more solvents (such as dipropylene glycol methyl ether acetate, propylene glycol phenyl ether acetate, ethylene glycol ethyl acetate) are added under a nitrogen environment, and the mixture is stirred at a speed of 500-1000 rpm.
[0009] S3, then reacting in a sealed manner at a high temperature of 120° C. for 4 hours, filtering and vacuum drying to obtain a MIL-101-acrylate composite.
[0010] Preparation of MIL-101-acrylate complex modified photoresist:
[0011] S4. Under nitrogen protection, the MIL-101-acrylate compound, epoxy resin, dye, photoinitiator, leveling agent and solvent were mixed in a certain proportion and stirred at a speed of 500 rpm for 1 hour.
[0012] S5. Add the further mixed product into the remaining solvent dipropylene glycol methyl ether acetate, and stir and mix at a speed of 600 rpm for 30 minutes to obtain a final photoresist.
[0013] As a preferred embodiment, the components of the negative photoresist (by weight ratio) can be adjusted as follows:
[0014] 1. 10-30 parts of MIL-101-acrylate compound;
[0015] 2. Epoxy resin (Su-8 epoxy resin) 20-40 parts;
[0016] 3. Dye (phthalocyanine) 1-5 parts
[0017] 4. Photoinitiator (benzoin dimethyl ether) 1-2 parts
[0018] 5. Leveling agent (polymethylphenylsiloxane) 0.1-0.5 parts
[0019] 6. Solvent (dipropylene glycol methyl ether acetic acid) 20-50 parts.
[0020] Compared with the prior art, the advantages of the present invention are:
[0021] 1. MIL-101 in the present invention is not a traditional MOF metal framework compound. It has extremely high flexibility and a "breathing" effect between two different configurations of large pores (lp) and narrow pores (np) during the adsorption process. The volume change can be as high as 40%, and the prepared composite also has a large volume tolerance.
[0022] 2. By combining epoxy resin with components such as MIL-101-acrylate complex, the present invention introduces a metal framework compound with a topological structure, which not only helps to solve the entanglement problem of the resin molecular chain, but also brings the potential for identification, authentication and barcode anchoring to the product. In addition, by coupling biotin or peptides, the photoresist can also have biological identifiability, adding a new dimension to the chip function.
[0023] Beneficial effects:
[0024] The present invention simplifies part of the preparation process, and no longer requires strict control of the molecular weight and uniformity of the epoxy resin, nor does it require further polymerization modification of the epoxy resin. Such improvements avoid a series of problems that may be caused by the modification process, making the production process more efficient and reliable.
[0025] Through these innovative preparation methods, the present invention also improves the storage stability of the photoresist, which is crucial for ensuring the quality of the product during storage and transportation.
[0026] In addition, the present invention also expands the application scope of epoxy resin in negative photoresist, improves the resolution and overall lithography performance of traditional photoresist resin, and significantly improves the accuracy and performance of the final product. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The figure is a flow chart of the preparation of the MIL-101-acrylate composite and the negative photoresist in the present invention. DETAILED DESCRIPTION
[0028] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0029] Example:
[0030] Preparation of MIL-101-acrylate composite:
[0031] Chromium nitrate nonahydrate (Cr(NO3)3·9H2O) and terephthalic acid (C8H6O4) were dissolved in deionized water at a molar ratio of 1:1, and hydrofluoric acid was added and stirred to form a mixed solution. Then, the mixed solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and a hydrothermal reaction was carried out at 220°C for 9 hours. After the reaction was completed, the reactor was allowed to cool naturally to room temperature, and MIL-101 was finally obtained after post-treatment steps such as centrifugation, washing and drying. MIL-101, polymethylphenylsiloxane and hydroxyethyl acrylate were mixed in a ratio of 1:0.1:10, and one or more solvents (such as dipropylene glycol methyl ether acetate, propylene glycol phenyl ether acetate, ethylene glycol ethyl ether) were added under a nitrogen environment, and the mixture was stirred at a speed of 500-1000rpm. Then, the reaction was closed at a high temperature of 120°C for 4 hours, and the product was obtained after filtration and vacuum drying.
[0032] Preparation of MIL-101-acrylate complex modified photoresist: MIL-101-acrylate complex, epoxy resin, dye, photoinitiator, leveling agent and solvent are stirred and mixed in a certain proportion, and the further mixed product is added to the remaining solvent to obtain the final photoresist.
[0033] Example 1
[0034] The formula and preparation method of Example 1 are as follows:
[0035] Formula: 20 parts of Su-8 epoxy resin, 10 parts of hydroxyethyl acrylate, 1 part of MIL-101, 1 part of phthalocyanine, 1 part of benzoin dimethyl ether, 0.1 part of polymethylphenylsiloxane, and 20 parts of dipropylene glycol methyl ether acetate.
[0036] Preparation method:
[0037] 1. Mixing: Under nitrogen protection, add 1 part of MIL-101, 0.1 part of polymethylphenylsiloxane, 10 parts of hydroxyethyl acrylate and 10 parts of dipropylene glycol methyl ether acetate into the reaction container at once. Heat to 120°C and stir and mix at 500 rpm for 4 hours. Filter and vacuum dry to obtain MIL-101-acrylate complex.
[0038] 2. Add the remaining components: Under nitrogen protection, add 20 parts of Su-8 epoxy resin, 1 part of phthalocyanine and 1 part of benzoin dimethyl ether to the mixture in step 1. Continue stirring and mixing at a speed of 500 rpm for 1 hour, then filter to remove undispersed particles, and dry under vacuum conditions.
[0039] 3. Final mixing: Add the complex obtained in step 2 to the remaining dipropylene glycol methyl ether acetate, and stir and mix at a speed of 600 rpm for 30 minutes to obtain a final photoresist.
[0040] 4. Photolithography: Use a 2μm scraper to evenly coat the photoresist on the pre-treated silicon wafer, bake for 10 minutes, and after ultraviolet light exposure, use 0.2% sodium carbonate developer to develop, and finally wash with pure water and debond with sodium hydroxide to obtain a photolithography pattern.
[0041] Example 2
[0042] The formulation and preparation method of Example 2 are similar to those of Example 1, but differ in the component proportions and the solvents used: 40 parts of Su-8 epoxy resin, 30 parts of hydroxyethyl acrylate, 5 parts of MIL-101, 2 parts of phthalocyanine, 2 parts of benzoin dimethyl ether, 0.5 parts of polymethylphenylsiloxane, and 50 parts of dipropylene glycol methyl ether acetate.
[0043] Example 3
[0044] The formulation and preparation method of Example 3 are similar to those of Example 1, but differ in the component proportions and the solvents used: 30 parts of Su-8 epoxy resin, 20 parts of hydroxyethyl acrylate, 3 parts of MIL-101, 1.5 parts of phthalocyanine, 1.5 parts of benzoin dimethyl ether, 0.3 parts of polymethylphenylsiloxane, and 35 parts of dipropylene glycol methyl ether acetate.
[0045] Comparative Example 1
[0046] The formulation and preparation method of Comparative Example 1 are similar to those of Example 1, except that the formulation does not contain MIL-101.
[0047] Comparative Example 2
[0048] The formulation and preparation method of Comparative Example 1 are similar to those of Example 1, except that polymethyl methacrylate is used instead of epoxy resin.
[0049] Comparative Example 3
[0050] The formulation and preparation method of Comparative Example 1 are similar to those of Example 1, except that the formulation does not contain polymethylphenylsiloxane.
[0051] Comparison example
[0052] The control example uses a negative photoresist product containing SU-8 resin sold on the market.
[0053] The test method is as follows: first, the resolution is detected according to the GB / T29556-2013 standard, and the smoothness and verticality of the photoresist edge are observed using an optical microscope. The results show that Examples 1-3 have better edge verticality than the comparison, representing better resolution. Then, the developed product is tested using the projection chrome plate method to detect the pinhole density to evaluate the product quality. The test is carried out after 2 minutes and 1 hour to verify the self-repair function of the photoresist.
[0054] Table 1: Sensitivity and pinhole density ratio of different photoresists (60min: 2min)
[0055]
[0056]
[0057] In addition, an accelerated aging test was performed to evaluate the stability of the photoresist products in the above examples: 10 grams of the product of each example was weighed and diluted with the solvent in the respective formulation to prepare 100 ml of a dilution solution. These diluted samples were placed in the same light-shielded bottle and stored in a light incubator at 35°C for 3 to 7 days. The clarity and color change of each sample dilution were compared with the refrigerated sample dilution solution, and the color change was recorded.
[0058] The test results show that the samples of Examples 1 to 3 and Comparative Example 3 did not change in appearance. Comparative Examples 1 and 4 began to turn yellow and the clarity decreased after 3 days of storage. The clarity of Comparative Example 2 and the control example decreased significantly after 7 days. These test results show that the photoresist compositions of Examples 1 to 3 have high resolution and sensitivity. The topological structures of these products are neatly arranged, the molecules are orderly, the edges are clear, the verticality is high, and they are suitable for thick glue processes. In addition, the topological structures can be used to add label substances to achieve the expansion of biometric recognition functions.
[0059] In the stability test, the negative photoresist product with the addition of MIL-101-acrylate complex shows better stability and preservation. However, the photoresist with the addition of other MIL products has poor preservation, which may be related to the special variable structure of MIL-101. In addition, the shelf life of Comparative Example 3 (the photoresist composition that does not form a complex but is simply mixed) is shorter and the stability is worse, which may be related to the fact that the metal oxide is more likely to absorb and scatter light, resulting in enhanced photosensitivity during storage. However, Examples 1 to 3 of the present invention can accommodate photosensitive initiators more stably under normal storage conditions. Pinhole density test also found that the product of the present invention has certain self-repairing properties, which is conducive to subsequent photolithography and has a positive impact on improving the product quality and wear resistance of the photoresist, and therefore has a wide range of research value and application prospects.
[0060] Unless otherwise specified, all percentages in the present invention represent weight percentages, and unless otherwise specified, solutions in the present invention refer to aqueous solutions. The numerical ranges in this application are approximate values, and specific examples are only listed. All possible combinations between the lowest value and the highest value listed are considered to be included in this application. Regarding the use of chemical compounds, unless explicitly stated, the singular form includes all isomeric forms, and nouns modified by adjectives such as "a" or "the" also include plural forms.
[0061] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a MIL-101-acrylate composite for negative photoresist, characterized in that The following steps are involved: S1. Dissolve chromium nitrate nonahydrate (Cr(NO3)3·9H2O) and terephthalic acid (C8H6O4) in deionized water at a molar ratio of 1:1, add hydrofluoric acid and stir evenly to form a mixed solution. Then, transfer the mixed solution to a stainless steel reactor lined with polytetrafluoroethylene and perform a hydrothermal reaction at 220°C for 9 hours. After the reaction is completed, let the reactor cool naturally to room temperature, and after post-processing steps such as centrifugation, washing and drying, MIL-101 is finally obtained. S2. MIL-101, polymethylphenylsiloxane and hydroxyethyl acrylate are mixed in a ratio of 1:0.1:10, and one or more solvents (such as dipropylene glycol methyl ether acetate, propylene glycol phenyl ether acetate, ethylene glycol ethyl acetate) are added under a nitrogen environment, and the mixture is stirred at a speed of 500-1000 rpm. S3, then react in a sealed manner at a high temperature of 120° C. for 4 hours, and obtain the MIL-101-acrylate composite after filtration and vacuum drying. Preparation of MIL-101-acrylate complex modified photoresist: S4. Under nitrogen protection, the MIL-101-acrylate compound, epoxy resin, dye, photoinitiator, leveling agent and solvent were mixed in a certain proportion and stirred at a speed of 500 rpm for 1 hour. S5. Add the further mixed product into the remaining solvent dipropylene glycol methyl ether acetate, and stir and mix at a speed of 600 rpm for 30 minutes to obtain a final photoresist.
2. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of MIL-101, polymethylphenylsiloxane and hydroxyethyl acrylate is 1:0.1:
10.
3. The preparation method according to claim 1, characterized in that: The acrylic acid ester monomer in step S2 is selected from one or more of hydroxyethyl acrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and methyl acrylate.
4. The preparation method according to claim 1, characterized in that: The reaction temperature in step S3 is 120° C. and the reaction time is 4 h.
5. The preparation method according to claim 1, characterized in that: The photoresist raw material in step S4 includes the following components by weight: 20-40 parts of epoxy resin, 10-30 parts of MIL-101-acrylate compound, 1-5 parts of dye, 1-2 parts of photoinitiator, 0.1-0.5 parts of leveling agent, and 20-50 parts of solvent.
6. The MIL-101-acrylate composite for negative photoresist prepared by the method according to any one of claims 1 to 5, characterized in that: Acrylate monomers and MIL-101 are used to form a composite.
7. The use of a MIL-101-acrylate composite for negative photoresist as claimed in claim 6, characterized in that: The composite formed by acrylate monomers and MIL-101 is used as a modified material for negative photoresist. It has neat edges, high resolution and self-repairing ability, and is used to improve the resolution and overall lithography performance of traditional photoresist resins.
Citation Information
Patent Citations
High-resolution negative photoresist and preparation method thereof
CN111736429A
Polymer resin and preparation method thereof, method for overcoming cracking of electron beam photoresist, electron beam photoresist as well as preparation and application of electron beam photoresist
CN113773433A
MIL-53-acrylate compound, negative photoresist and preparation method
CN117826533A
Enhanced negative photoresist and preparation method thereof
CN118151491A
Negative photoresist used for semiconductor encapsulation process
US20210018838A1